Excision of abdominal wall recurrence of uterine leiomyosarcoma: A case report - Sahana Punneshetty,; Rachel G Chandy,; Geley Ete,; Suchita Chase,; Anjana Joel,; Abraham Peedicayil, (Indian Journal of Case Reports, 2021)
The literature on management of recurrent/metastatic uterine leiomyosarcomas is limited and metastasis to the abdominal wall is very rare. We operated on a 46-year-old woman who had a total abdominal hysterectomy elsewhere for a uterine tumor and presented with recurrence to the anterior abdominal wall, 9 months after the primary surgery. There were two large ulcerated abdominal wall masses. The challenge after complete excision of the tumor was to reconstruct the abdominal wall. We were able to close the defect with a dual mesh and a fasciocutaneous flap from the anterolateral thigh. She received adjuvant chemotherapy with gemcitabine and docetaxel. At the completion of chemotherapy, she was well and apparently disease free. She recurred in the left inguinal node after 9 months but responded to oral pazopanib followed by chemotherapy. This case report highlights the rare possibility of abdominal wall metastasis after initial surgery for leiomyosarcoma. It shows that good quality of life can be achieved by a multidisciplinary treatment of abdominal wall metastasis of uterine leiomyosarcoma.